Wolbachia Tertunda: Analisis Faktor Penghambat Implementasi Program - Novayanti, Luh Herry; Widhiasthini, Ni Wayan (Universitas Sultan Ageng Tirtayasa, 2024)
The utilisation of Wolbachia as a technological innovation to reduce dengue cases in Buleleng district has encountered challenges in its implementation. This study aimed to explore the factors influencing collaborative governance. This research employed a qualitative approach with a case study as the research design. Data were collected through in-depth interviews with 11 informants representing various stakeholders, including local government, non-governmental organisations, community, and mass media. This study identified ineffective leadership, unclear regulations and policies, limited community participation, reliance on the private sector, suboptimal evaluation and monitoring, and limited competent human resources as significant critical issues in the implementation of the Wolbachia programme. Ineffective leadership, both at the central and local levels, resulted in an unclear vision, lack of commitment and poor communication, which ultimately hindered collaboration and programme effectiveness. Based on these findings, this study presents several recommendations to enhance collaborative governance in Wolbachia implementation. These include strengthening leadership and coordination, improving regulations and policies, increasing community participation, strengthening the role of local government, and increasing transparency and accountability in programme evaluation and monitoring. It is anticipated that this research will contribute to the development of a more effective and sustainable Wolbachia implementation strategy.